Environmental awareness in children at the elementary level. An educational experience - Guzmán Caycho, Sonia Marlene (2023)
Pollution and environmental deterioration have become the biggest problems in the contemporary world and constitute the thematic reference to be addressed by the educational field. The objective of the research was to propose an educational program to improve environmental awareness in children at the initial level. A qualitative methodology was determined by interviewing teachers and directors, whose perceptions were optimally triangulated. The results showed that there is a need to promote the development of the cognitive, affective, active and conative dimensionality of children at the initial level, who develop in a neglected and abandoned environment. It was concluded that the formulation of proposals with pedagogical intention allows the development of valid attitudes and knowledge; The proposal of various environmental educational activities positively improves the behavior of children in promoting the care and preservation of the environment where they operate daily.